Konsep Amtsâl Al-Qur’an Nûr Al-Dîn 'Itr dalam Karyanya ‘Ulum Al-Qur’an Al Karîm - Vera Oktafiani; Akhyar Hanif (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The main problem in this paper is Amtsal, which is the style of the Qur'anic language by providing parables. The purpose of this study is to describe and analyze the concept of amtsal Nûr Al-Dîn 'Itr in his work 'Ulum al-Qur'an al-karîm. The type of research that the author uses is library research with the analysis method of character study interpretation. The primary data source in this research is the book 'Ulum al-Qur'an al-karim by Nûr Al-Dîn 'Itr. From the research that the author conducted, it can be concluded that: (1) The majority of scholars limit Amtsal only to the concept of taswir sentences, while others do not include Amtsal in their discussion of the Qur'an. (2) Nûr Al-Dîn 'Itr includes the discussion of Amtsal in his book 'Ulum al-Qur'an al-karim in the sciences of the Qur'an, while others include the discussion of mutlaq muqayyad, mantuq mafhum which discussion This is a discussion in the science of ushul fiqh.